2020
DOI: 10.1186/s13023-020-01466-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiovascular involvement on the clinical course of paediatric mitochondrial disorders

Abstract: Background Primary mitochondrial disorders (PMD) are rare conditions resulting in progressive multi-organ failure. Cardiovascular involvement (CVI) has been reported in paediatric patients. However, its age-related prevalence, clinical presentation and prognostic impact are unresolved. We detailed CVI in a cohort of children diagnosed with PMD over two decades at a tertiary referral centre. Results We enrolled 86 PMD patients (M/F = 30/56; mean age 6.4 ± 8.58 years). CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Primary mitochondrial diseases (PMDs) are a heterogeneous group of afflictions caused by anomalies in the mitochondrial respiratory chain or in cellular oxidative phosphorylation [15][16][17]. Mitochondrial DNA (mtDNA) codes for part of the subunits forming the five complexes, and the remaining parts are synthesized from nuclear gene transcripts [18][19][20].…”
Section: Nutritional Approaches In Primary Mitochondrial Diseasesmentioning
confidence: 99%
“…Primary mitochondrial diseases (PMDs) are a heterogeneous group of afflictions caused by anomalies in the mitochondrial respiratory chain or in cellular oxidative phosphorylation [15][16][17]. Mitochondrial DNA (mtDNA) codes for part of the subunits forming the five complexes, and the remaining parts are synthesized from nuclear gene transcripts [18][19][20].…”
Section: Nutritional Approaches In Primary Mitochondrial Diseasesmentioning
confidence: 99%
“…Heart disease was observed to be more common in male children with specific mitochondrial conditions (Barth syndrome, TMEM70 mutations, and MELAS). Non-compaction, hypertrophic, and dilated cardiomyopathies were the prevalent conditions, while pulmonary arterial hypertension was less frequent [40].…”
Section: Mitochondrial Cardiomyopathiesmentioning
confidence: 99%
“…Mitochondrial diseases comprise a multisystemic group of metabolic disorders characterized by early- or late-onset progressive neurodegenerative and cardiac symptoms, likely associated with a psychomotor regression, encephalopathy, myopathy and cardiomyopathy ( DiMauro and Schon, 2013 ). Around 20–40% of children with a mitochondrial disease develop a kind of cardiac symptoms ( Brambilla et al, 2020 ; Mazzaccara et al, 2021 ). In such cases, severity is quite variable ranging from asymptomatic status to severe manifestations including heart failure, arrhythmias, and sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, epidemiological studies demonstrated that mutations in mitochondria-related genes including single-nucleotide variants to large-scale deletions, affect 1 in 4,500 individuals ( Chinnery et al, 2000 ), and the risk to develop cardiac symptoms is significantly higher in this patient cohort. Furthermore, a clinical study showed that 36% of patients with mitochondrial disorders harboring mutations in nuclear DNA- or mtDNA-encoded genes developed a kind of cardiomyopathy ( Brambilla et al, 2020 ), probably due to the high bioenergetic demand required by the heart. At the same time, infants with cardiovascular compromise in mitochondrial deficiency display a worse late survival compared to patients without cardiac compromise and current therapies are unable to substantially mitigate the disease burden ( Wahbi et al, 2015 ; Brambilla et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation